Efeito da infestação de macrófitas aquáticas na comunidade planctônica em um viveiro de piscicultura - Boareto, Cecília Anatriello [UNESP] (2014)
The invasions of macrophytes are recurrent and cause various implications in freshwater ecosystems. The aim of the study was to evaluate if two types of invasions of macrophytes, one monospecific and other heteroespecífica, occurred naturally in a pond, changed the chemical, physical and biological variables of the water, compared to the period of absence of macrophyte. In the first invasion of macrophytes, the samples were collected during periods with and without macrophytes weekly during the months of February, March, May and June 2009, and it were collected samples of water and zooplankton. In the second invasion of macrophyte, the samples were collected during periods with and without macrophytes, monthly, during the months of May 2010 to February 2011, and it were collected samples of water and zooplankton and phytoplankton communities. Results from the first invasion by S. auriculata showed that the floating macrophyte caused negative changes in the concentrations of the physical and chemical parameters and selected the tolerant species to wide variations in the aquatic environment (Filinia terminalis, Lecane proiecta, Trichocerca longiseta and Thermocyclops decipiens). In the period of absence from S. auriculata the concentration of dissolved oxygen increased, decreased concentrations of organic matter, thermotolerant coliform and ammonia, which provided the occurrence mainly Cladocera (Daphnia gessneri and Diaphanossoma birgei), which is a good live food available in the water. In the second invasion, the presence of emergent and floating macrophytes decreased mainly concentration of organic matter, favoring the occurrence of Cladocera (Alona monacantha), Copepoda (Cyclopoida and Calanoida nauplii) and greater abundance of Chlorophyceae. These factors provide a higher quality of live food available in the water. Already in the absence of these plants, the concentrations of some variables aumentararam and were essential to ...